Fragmentation dynamics of doubly charged camphor molecule following C 1s Auger decay. Issue 5 (25th January 2022) - Sen, Sanket; Mandal, S.; Sen, Arnab; Gopal, R.; Ben Ltaief, L.; Turchini, S.; Catone, D.; Zema, N.; Coreno, M.; Richter, R.; Mudrich, M.; Krishnan, S. R.; et al.
Abstract : Investigation of the fragmentation of doubly charged camphor molecule following C 1s Auger decay experimentally by VMI-PEPIPICO, supplemented with MD simulations. Abstract : The fragmentation dynamics of the gas-phase, doubly charged camphor molecule, formed by Auger decay following carbon 1s ionisation, using soft X-ray synchrotron radiation, is presented in this work. The technique of velocity map imaging combined with a photoelectron–photoion–photoion coincidence (VMI-PEPIPICO) is used for both electron energy and ion momentum (in-sequence) measurements. The experimental study is complemented by molecular dynamics simulation, performed with an NVT (moles, volume, and temperature) ensemble. Velocity Verlet algorithms were used for time integration at various internal energies. These simulations validate observed dissociation pathways. From these, we successfully deduce that the internal energy of the doubly charged molecular ion has a significant contribution to the fragmentation mechanism. Notably, a prominent signature of the internal energy was observed in the experimentally determined energies of the neutral fragment in these deferred charge separation pathways, entailing a more detailed theoretical study to uncover the exact dissociation dynamics.